A Case of Hemophagocytic Lymphohistiocytosis in a Patient with Chronic Lymphocytic Leukemia after Treatment with Fludarabine, Cyclophosphamide, and Rituximab Chemotherapy, with Autopsy Findings - Ing S. Tiong; Michael B. Y. Lau; Seventeen Toumoua; Shingirai Chiruka (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH) is rarely described in association with chronic lymphocytic leukemia (CLL), mostly triggered by disease progression or concurrent infection. A 68-year-old male received 4 cycles of fludarabine, cyclophosphamide, and rituximab (FCR) for CLL and achieved a complete response. Twenty-four days after the last chemotherapy, he presented with febrile neutropaenia and was diagnosed with HLH. The diagnosis was based upon persistent fever, pancytopenia, hyperferritinemia, splenomegaly, and hemophagocytosis on bone marrow aspirate. He began treatment with dexamethasone, cyclosporine, and etoposide. Fever resolved and hyperferritinemia improved but pancytopenia persisted. He died 13 days later from septic shock with positive blood cultures. A limited postmortem examination was performed and biopsies were taken from bone marrow, liver, and spleen. Biopsies demonstrated abundant hemophagocytosis by the activated macrophage as stained by CD68. There was no evidence of residual CLL as demonstrated by the lack of lymphocytes which was confirmed by the negative staining of CD79a. Chemotherapy appears to be responsible for the development of HLH in this patient. This is the second reported case of HLH developing after a rituximab-containing chemotherapy.